Radiation dose required for the vulcanization of natural rubber latex via hybrid gamma radiation and peroxide vulcanizations - Sofian, Ibrahim; Khairiah Haji, Badri; Chantara Thevy, Ratnam; Noor Hasni, M. Ali; Muhammad Abdurrahman, Munir (IOP Publishing Ltd, 2019)
To enhance the crosslinking of prevulcanized natural rubber latex, combination of Irradiation and peroxide vulcanizations were used. Through this method, hexanediol diacrylate (HDDA) from irradiation vulcanization acted as the main sensitizer, while cumene hydroperoxide (CHPO) from peroxide vulcanization would act as the co-sensitizer. The effects of irradiation doses on the mechanical properties of latex film were investigated. 16 kGy irradiation dose, 2.5 parts perhundred rubber (pphr) of HDDA, 0.1 pphr of CHPO and 2.5 phr of Aquanox LP antioxidant were found to be the optimum conditions for compounding formulation. The rubber film obtained had tensile strength, modulus at 500% and modulus at 700% of 27.7, 3.5 and 12.4 MPa respectively, which is more than 21% increment compared to control film. Besides, the crosslink percentage of the rubber film showed 7 % increment from 90.7% to 97.7%.